Notes on Old Turkic 'Dongoin Shiree'Inscriptions Newly Discovered at Mongolia - Olmez, Mehmet (ISTANBUL UNIV, 2017)
Every passing year, researchers make important discoveries on the inscriptions in the past 25 years, with an increase in field works, we continue getting some new further information on the inscriptions already known and also hearing about the newly-introduced ones. The subject of this paper is one of the latter, Dongoin Shiree an inscription introduced in 2010-2011 and published in 2015. Although there are more than 1100 words written on this inscription, the total vocabulary of it consists of a maximum of 20 words. Among those 20 words, eleLATIN SMALL LETTER ENGime is one of the words which are hard to explain. In this short paper, we will suggest an explanation for the word in question.
Keywords: Old Turkic runic inscriptions; 2nd Tukic Qaghanate; Old Turkic Tamgas; Dongoin Shiree inscriptions; Linguistics; Literature